Contribution to the inventory of the entomofauna of the Lokoli swamp forest (Benin). Second Supplement: Rhopalocera (Lepidoptera, Rhopalocera, Papilionoidea) - (:unkn) unknown (My University, 2022)
For more than twelve years, we prospected the flooded forest of Lokoli, located in the commune of Zogbodomey, in Benin. We have studied the rhopalocere Lepidoptera more particularly: we provide the list of the 227 species identified and present the most interesting.
Keywords: African Research